Technical crystallization for application in pharmaceutical material engineering: Review article - Abdul Khaliq El-Z; Hind El-Zein (Elsevier, 2015)
In recent years, engineering the total morphology of pharmaceutical materials particles to desirable shape, size and surface area has long been actively increased because it has many advantages especially for improving physicochemical properties of Active Pharmaceutical Ingredients (APIs). This article therefore considers the potential utility of crystal engineering as a tool for controlling and designing properties of pharmaceutical solid particles in purpose to developing efficacious performance of solid dosage form, fundamentals of crystallization process, applications. In addition, understanding the relationship between molecular recognition, thermodynamic, and kinetics which controls the crystallization process so that it benefits in designing successful experiments to have desirable crystal habit for materials.